Social Media Integration and Financial Performance of Selected Micro Retail Businesses in Cebu City - Lumbab, Raul Jr; Zamora, Julie Mae; Jucom, Louise Nichole; Sapariya, Junaline (Future Science / FSH-PH Publications, 2024)
The tremendous shift towards digital platforms has prompted businesses to go online during the heights of the pandemic. Among those who embraced this enormous shift are the Micro, Small and Medium Enterprises (MSMEs), which are the backbone of the economic growth in developing countries. The efficient use of social media marketing has been a key player in the success of companies in today’s business environment, and the quest for sustainable development gives rise to the need for better strategic decisions in the MSMEs. This paper analyzes whether there is a relationship between social media integration and the financial performance of selected micro retail businesses in Cebu City. The level of social media integration and the total assets turnover of 385 selected micro retail businesses were correlated using Pearson’s correlation, with their related advertising expenses as the moderating variable. As observed in a non-contrived setting with minimal interference, our results showed a weak positive correlation among the variables correlated with such relationships varying per business industry. Our analysis also revealed that the average total assets turnover of businesses employing social media is higher than those which do not. The results also showed that the more integrated the business is, the more likely they are to invest in social media advertising.